The Role of Teacher-student Relationship in Motivation (A Case Study of Community School of Nepal) - Rawal, Shankar Bahadur (AMC Multidisciplinary Research Journal, 2022)
This research paper is focused to analyze how teachers - students’ relationship plays a crucial role in students’ motivation in learning. This paper is based on the Gardner model of motivation. By adopting a qualitative method approach and a phenomenological research design, the research paper has been prepared. Convenience sampling technique has been used in it. Data were collected by using a questionnaire and unstructured interview via telephone. Four issues were identified between the teachers-student’s relationships throughout the unstructured interview: the importance of teacher-student relationship, teacher expectation, students’ motivation, and improvement in academic learning. The delimitation of this researcher was to collect the data from the telephone call due to the high transmission and risk of communicable diseases like corona virus (COVID -19) spreading all over the world. The research found out that, the better contact and mutual relationship between teachers and students resulted higher motivation in learning.